EU-Wide Cross-Sectional Observational Study of Lipid-Modifying Therapy Use in Secondary and Primary Care: the DA VINCI study. (28th August 2020) - Ray, Kausik K; Molemans, Bart; Schoonen, W Marieke; Giovas, Periklis; Bray, Sarah; Kiru, Gaia; Murphy, Jennifer; Banach, Maciej; De Servi, Stefano; Gaita, Dan; Gouni-Berthold, Ioanna; Hovingh, G Kees; et al.
Abstract: Aims: To provide contemporary data on the implementation of European guideline recommendations for lipid-lowering therapies (LLTs) across different settings and populations and how this impacts low-density lipoprotein cholesterol (LDL-C) goal achievement. Methods and results: An 18 country, cross-sectional, observational study of patients prescribed LLT for primary or secondary prevention in primary or secondary care across Europe. Between June 2017 and November 2018, data were collected at a single visit, including LLT in the preceding 12 months and most recent LDL-C. Primary outcome was the achievement of risk-based 2016 European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) LDL-C goal while receiving stabilized LLT; 2019 goal achievement was also assessed. Overall, 5888 patients (3000 primary and 2888 secondary prevention patients) were enrolled; 54% [95% confidence interval (CI) 52–56] achieved their risk-based 2016 goal and 33% (95% CI 32–35) achieved their risk-based 2019 goal. High-intensity statin monotherapy was used in 20% and 38% of very high-risk primary and secondary prevention patients, respectively. Corresponding 2016 goal attainment was 22% and 45% (17% and 22% for 2019 goals) for very high-risk primary and secondary prevention patients, respectively. Use of moderate–high-intensity statins in combination with ezetimibe (9%), or any LLT with PCSK9 inhibitors (1%), was low; corresponding 2016 and 2019 goal attainment was 53% and 20% (ezetimibe combination), and 67% and 58% (PCSK9i combination). Conclusion: Gaps between clinical guidelines and clinical practice for lipid management across Europe persist, which will be exacerbated by the 2019 guidelines. Even with optimized statins, greater utilization of non-statin LLT is likely needed to reduce these gaps for patients at highest risk.